Conference proceedings - Kabuka, Solomon ed. ([s.n.] [S.l.], 1993)
Focuses on aspects such as public policy on energy; energy economics; manufacturing and trade of energy products; agricultural and environmental sustainability; energy efficiency technology for buildings; and, energy technology in the Caribbean.